Culture change towards construction safety risks, incidences and injuries: best practice experiences - Mahmud, Syamsul Hendra; Misnan, Mohd Saidin; Wan Mahmood, Wan Yusoff; Bakri, Ahmadon (2008)
The construction industry has a reputation as one of the most dangerous industries because of its high rates of incidents, injuries and fatalities. Recently, many approaches have been adapted by construction companies but most of them were focused on physical working conditions and safety management system/procedure. An improvement to safety will only be achieved if all project stakeholders recognise the need to change their belief, attitude, commitment and behaviour to create a good safety culture. This paper presents a literature review to highlight the need for a culture change towards better construction safety. The paper then presents case studies on two construction management company - Bovis Lend Lease and Bechtel Corporation as strategies for developing good construction safety culture, which includes the objectives, strategies, context and implementation process as well as lessons learned. It is concluded that it is crucially important to develop a good construction safety culture through changing the employees’ belief, attitude, commitment and behaviour. Therefore construction safety managers need to adapt more holistic strategies which focus on not only improving physical working environment and employees’ safety knowledge, but also on shaping employees’ beliefs and attitude which lead to safe behaviour and ultimately healthy safety culture.